Pengaruh Prenatal Gentle Yoga Terhadap Pengurangan Keluhan Ketidaknyamanan Pada Ibu Hamil Trimester III - Suryamah Laelasari; Wintarsih Wintarsih (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Background :. Pregnancy is a gift that is coveted by all women, but not all married women can experience pregnancy. During pregnancy, the mother experiences changes that can cause discomfort, especially in the third trimester. There are several ways of handling complaints during pregnancy, one of which is yoga. For this reason, researchers are interested in examining prenatal gentle yoga on the level of maternal discomfort in the third trimester of pregnancy. Purpose of Writing:. Knowing the effect of Prenatal Gentle Yoga on reducing / not reducing complaints of discomfort in third trimester pregnant women Research Methods: This study was conducted from January to February 2022, a sample of 15 pregnant women in the third trimester who took the Prenatal Gentle Yoga class at the Nabila Clinic, Karawang. This study uses a pre-experimental method with a one-group pretest and posttest design approach. Results: Complaints of discomfort during the third trimester of pregnant women before doing prenatal gentle yoga and after doing prenatal gentle yoga, most of the pregnant women in the third trimester felt a change. Wilcoxon statistical test results obtained prob value. (0.001) is much lower than 0.05 or (p<Î±), this means that there is an effect before and after the Prenatal Gentle Yoga class at Nabila Clinic.